Retrospective Analysis on the Use of Amphotericin B Lipid Complex in Neutropenic Cancer Patients with Suspected Fungal Infections in Lebanon, a Single Center Experience and Review of International Guidelines - Moghnieh, Rima; El-Rajab, Nabila; Abdallah, Dania Issam; Fawaz, Ismail; Mugharbil, Anas; Jisr, Tamima; Ibrahim, Ahmad (Frontiers in Medicine, 2016)
Introduction: Immunocompromised patients carry a high risk for invasive fungal disease (IFD), which is associated with high mortality. Materials and Methods: This is a retrospective chart review of a 4 years’ experience of ABLC utilization for the management of suspected IFD at the Hematology/Oncology and Bone Marrow Transplantation unit at Makassed General Hospital, Beirut, Lebanon between January 2011 and December 2014. We focused on treatment strategy, response rate and adverse drug events associated with ABLC therapy. We also reviewed ABLC indications in international guidelines beyond its Food and Drug Administration approval. Results: A total of 89 patients received ABLC therapy for suspected fungal infection. Forty eight percent (48%) were treated for a possible fungal infection, 19% for a problable fungal infection, 12% based on hospital guidelines, and 20% based on treating physician’s recommendations. The overall response rate was 71%. Nephrotoxicity occurred in 24% of patients and serum creatinine improved in 10% of these patients. Moderate hypokalemia was observed in 61% of the patients and severe hypokalemia in 10% but was corrected in both cases. Hepatotoxicity was observed in 12% of the patients throughout ABLC therapy. Drug delivery reactions were observed in 36% of the patients. There was a decrease in the incidence of these reactions upon using combination of premedication drugs. Conclusion: In this study, ABLC proved to be an effective and safe option in the management of suspected IFD in immunocompromised patients failing previous therapies.